SAT0149 Biologic Therapy: Switching and Dose Modification in Refractory Uveitis of Behcet'S Syndrome. Multicenter Study of 108 Patients. (23rd January 2014) - Calvo-Río, V.; Blanco, R.; Beltran, E.; S-Bursón, J.; Mesquida, M.; Adán, A.; Hdez-Grafella, M.; Valls, E.; Mtnez-Costa, L.; Sellas, A.; Cordero-Coma, M.; D-Llopis, M.; et al.
Abstract : Background: In patients undergoing a biologic due to uveitis associated to Behçet´s syndrome (BS) may occurr: a)switched to another because of insufficient response (IR), toxicity, or change in the route of administration, b)discontinuation or reduction of dose due to remission. Objectives: To study these situations in a large series of BS patients. Methods: Study of 108 patients with uveitis refractory to conventional therapy who required at least 1 biologic. Standard dose of Infliximab (IFX): 5 mg/k/iv at 0, 2, 6 and every 4-8 weeks, Adalimumab (ADA) 40 mg/sc/2 weeks, golimumab (Goli) 50 mg/4 weeks, tocilizumab (TCZ) 8 mg/kg/iv/4 weeks and rituximab (RTX) 1g/iv/15 days (2 doses) every 6 months. Results: Biologic used as the 1st choice: IFX (65 patients) or ADA (43). IFX-treated patients received IFX at 5 mg/k/i.v. (59 cases), 3 mg/kg (5), IFX 4 mg/kg (1). Initial IFX was changed to another single biologic in 26 cases; 24 to ADA, 1 to RTX, and 1 to etanercept. The initial ADA was changed to another single biologic in 6 cases; 2 to Goli, 4 to IFX and 1 to TCZ. In 3 cases there was a double biologic switching, ADA to Goli and to IFX (2 cases) and IFX to ADA and to TCZ (1 case). Improvement was achieved in: 9 of 11 patients with switching from IFX to ADA because of IR and in 2 of the 3 switched from ADA to another biologic. In 54 (50%) patients in persistent remission the dose was reduced or discontinued. IFX was decreased from 5 to 3 mg/k/iv (4 patients) or the interval was increased (22 patients). ADA interval was increased for more than 2 weeks (11 patients). Biologic was discontinued in 17 cases (11 IFX and 6 ADA). After a mean follow-up of 10.4±8.7 months after discontinuation, 13 of 17 remained on remission while 4 had a flare that led to the resumption of the same agent achieving remission again. Conclusions: Switching of biologic agents may be useful. Once clinical remission is achieved, dose reduction or discontinuation of the biologic may be obtained Disclosure of Interest: None Declared